Urgensi Pendidikan Agama Islam dalam Menyikapi Digitalisasi - Mardiah Astuti; Fajri Ismail; Herlina Herlina; Binti Rizqi Dinianti; Anggun Rahmadani (Departement of Mathematics Education, 2024)
In the era of rapid digitalization and technological advancement, the significance of Islamic Religious Education (IRE) becomes increasingly urgent in shaping the character and morality of students. This study aims to identify the critical role of IRE in addressing various challenges arising from digitalization, such as cyberbullying and the erosion of moral values. The research employs a literature review method, analyzing various literatures and studies focused on the role of IRE in the digital age. The findings reveal that IRE not only serves as a medium for religious learning but also as a pillar for building students' character, enabling them to use technology wisely and ethically. Religious teachers play a vital role in guiding students to understand and apply religious values in their digital lives. Therefore, the integration of strong religious education and character-building in the curriculum is essential to prepare students for the digital era with a solid moral foundation. It is crucial to have a comprehensive approach to teaching IRE that can respond to the dynamics of digitalization, so students can grow into individuals with strong character and the wisdom to navigate the challenges of the digital world.